2010
DOI: 10.2193/2008-475
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Spotted Owls in the Sierra Nevada, California

Abstract: The California spotted owl (Strix occidentalis occidentalis) is the only spotted owl subspecies not listed as threatened or endangered under the United States Endangered Species Act despite petitions to list it as threatened. We conducted a meta‐analysis of population data for 4 populations in the southem Cascades and Sierra Nevada, California, USA, from 1990 to 2005 to assist a listing evaluation by the United States Fish and Wildlife Service. Our study areas (from N to S) were on the Lassen National Forest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 52 publications
(115 reference statements)
7
54
1
Order By: Relevance
“…We used a 20-year (1991 to 2010) dataset collected as part of a long-term demographic study of California Spotted Owls in the central Sierra Nevada (Seamans et al 2001, Seamans andGutiérrez 2007) to test these hypotheses. Previous studies have shown that our study population exhibits biennial cycles in reproductive output (Blakesley et al 2010), a finding that was supported by an analysis of the 20-year dataset we considered here (Appendix A, Appendix A Figure 4). …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…We used a 20-year (1991 to 2010) dataset collected as part of a long-term demographic study of California Spotted Owls in the central Sierra Nevada (Seamans et al 2001, Seamans andGutiérrez 2007) to test these hypotheses. Previous studies have shown that our study population exhibits biennial cycles in reproductive output (Blakesley et al 2010), a finding that was supported by an analysis of the 20-year dataset we considered here (Appendix A, Appendix A Figure 4). …”
Section: Introductionsupporting
confidence: 86%
“…Moreover, many Spotted Owl populations exhibit regionally synchronized, annual cycles in reproductive output, in which good reproductive years tend to be followed by bad reproductive years (i.e. an ''even-odd'' pattern; Anthony et al 2006, Blakesley et al 2010, Forsman et al 2011) that may represent the emergent effect of reproductive costs (Forsman et al 2011). Following a ''good'' year in which most individuals in the population breed, impacts to body condition stemming from reproductive costs could reduce breeding propensity in a large segment of the population during the subsequent year, resulting in low population-level output.…”
Section: Introductionmentioning
confidence: 99%
“…In the study area, the California spotted owl (Strix occidentalis occidentalis), northern goshawk (Accipiter gentilis), and California populations of fisher (Martes pennanti ) are carnivores whose life histories include a close association with old forest and complex forest structure, primarily in mixed conifer forests. Current population sizes of these species are small and population growth rates are near zero or negative (Blakesley et al 2010. These conditions have led to controversy, litigation, and a resultant agency ''hands off'' policy towards these species that is focused on avoiding the short term putative threats of active forest management.…”
Section: Implications For Managementmentioning
confidence: 99%
“…To assess demographic rates and explore ecological relationships, biologists have surveyed California Spotted Owl sites annually for more than 20 years in three areas of the Sierra Nevada (see Blakesley et al 2010). In other areas of the Sierra Nevada, biologists with the U.S. Forest Service (USFS) surveyed historically occupied Spotted Owl sites prior to forest management such as logging.…”
Section: Introductionmentioning
confidence: 99%